Effect of furnace temperature on iron nugget production under semi-fusion conditions - Benkli, Yunus Emre; Boyrazli, Mustafa; Cizmecioglu, Zeki (University of Chemical Technology and Metallurgy, 2018)
This study has been conducted to determine whether iron nugget having similar features to pig iron that can be obtained after a period of nearly 8 hours under blast furnace conditions, could be obtained in shorter period. In our previous study, iron nugget was produced using carbon composite pellets obtained from magnetite ore at furnace temperature 1330°C and furnace residence time 48 minutes. In this study the carbon composite pellets, produced using magnetite iron ore and coke through reduction at semi-fusion conditions, were used for production of iron nugget at furnace temperature 1410°C and residence time 8 minutes. The reduction was carried out under semi-fusion conditions in order to produce an iron nugget having physical and chemical features that are similar to high furnace pig iron at lower temperature and furnace residence time. The iron nugget was produced from pellets composed of iron oxide, coke, flux, and binder. Its characteristics are: micro hardness of 343.4 HV, apparent density of 6.786 and iron content of 92.7 %. © 2018, University of Chemical Technology and Metallurgy.
Keywords: Cold bonded composite pellet; Iron nugget; Iron ore; Pelletizing